2008
DOI: 10.1249/mss.0b013e31815a5181
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Supplementation and Anabolic Steroid Use in Adolescents

Abstract: This study demonstrates that reliance on nutritional supplements increases as adolescents mature. The apparent willingness of adolescents to use a supplement that may harm their health or shorten their life highlights the need for greater involvement of teachers, coaches, and physicians to provide continued education on the risks and benefits associated with nutritional supplementation and AS use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
98
1
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 22 publications
11
98
1
11
Order By: Relevance
“…This is similar to vitamin/mineral use in US adolescents where almost three-fifths of them used such products (12) . In Korea, 35?8 % of 17-year-old students used VMS (30) .…”
Section: Adolescents' Use Of Vitamin/mineral Supplementssupporting
confidence: 54%
“…This is similar to vitamin/mineral use in US adolescents where almost three-fifths of them used such products (12) . In Korea, 35?8 % of 17-year-old students used VMS (30) .…”
Section: Adolescents' Use Of Vitamin/mineral Supplementssupporting
confidence: 54%
“…O principal objetivo dos usuários é ganhar massa muscular, o que vai ao encontro da finalidade mais citada para o uso de suplementos (13,17,21,22) . Atualmente, a maioria das pessoas (especialmente as mulheres) se exercita para controlar o peso e não para melhorar o condicionamento físico.…”
Section: Discussionunclassified
“…Ele aparece citado em todos os suplementos, especialmente os protéicos. O treinador também é a maior fonte de indicação em outros estudos (13,16,(21)(22)(23)27) .…”
Section: Discussionunclassified
“…This suggests that users of legal supplements are at a much higher risk of using illegal drugs. This finding is notable when one considers the widespread use of legal supplements across all levels of sport [101][102][103][104]. In a recent study, Backhouse et al [23] suggested that a gradual increase in nutritional supplements' consumption served as a gateway to doping use.…”
Section: Effect Sizes Of Demographic and Social-contextual Variablesmentioning
confidence: 99%